Peran Media Sosial Sebagai Ruang Publik: Tinjauan Filosofis Gagasan Ruang Publik Jürgen Habermas - Setiawan, FX. Rudi (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2023)
Jürgen Habermas is a second generation Frankfurt critical theory thinker who offers a new paradigm of critical theory, namely communication. He made an important contribution to the democratic life of complex and pluralistic contemporary society through his theory of communicative action. It offers a procedure for communicating through rational discourse to reach an intersubjective agreement. In a modern democratic country, public space becomes a forum where public opinions and aspirations are conveyed through rational argumentation as a form of control by citizens over the government. This public space is independent and free from state or market control. This article is an analysis of social media and its potential role as a public space, using Habermas’ theoretical framework. Social media has the potential to become a political public space because of its participatory character. Even though implementing social media as a public space is still difficult, social media still has a big influence on democracy and social change. Therefore, social media users need to have and develop their social media literacy which is based on the principles of solidarity, criticality and caution.